English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I'm having lots of trouble with this one. Any help would be appreciated.

Integral of:

3x^2-6
--------- dx
(x+1)(x-2)

2006-10-05 10:35:18 · 3 answers · asked by Quiet Amusement 4 in Science & Mathematics Mathematics

3 answers

First divide to get a quotient and a remainder where the remainder has degree less than that of the denominator. In this case, you will be dividing 3x^2-6 by x^2-x-2 to get 3+3x/(x+1)(x-2). Now do the partial fractions decomposition on the second piece. So you want to write
3x/(x+1)(x-2)=A/(x+1) +B/(x-2).
Multiply by (x+1)(x-2) to get
3x=A(x-2)+B(x+1).
Let x=2 to find B=2 and let x=-1 to find A=1.
Thus, you are integrating
3+ 1/(x+1) +2/(x-2).

2006-10-05 11:02:13 · answer #1 · answered by mathematician 7 · 0 0

Let (3x^2-6)/[(x+1)(x-2)] = A/(x+1) + B/(x-2), where A and B are constants to be determined.

Multiply both sides by the original denominator, and get

3x^2-6 = A(x-2) + B(x+1).

Now, use the "method of creating zeros". Let x=2. Then the term with A will drop out, and you can solve for B. Then, go back to the equation above, plug in x=-1, and the term with B will drop out, and you can get A.

Once you have A and B, you can integrate A/(x+1) + B/(x-2), using the rule

integral of 1/(x+a) dx = ln |x+a|

and you're done.

2006-10-05 10:44:35 · answer #2 · answered by James L 5 · 1 0

integral of 3x^2-6/(x+1)(x-2)=3x^2-6/x^2-x-2
dividing x^2-x-2)3x^2 -6(3
3x^2-3x-6
----------------
3x
so the expression reduces to 3+[3x/(x+1)(x-2)]
let A/(x+1)+B/(x-2)=3x/(x+1)(x-2)
A(x-2)+B(x+1)=3x
comparing the coefficients
A+B=3
-2A+B=0
3A=3 so A=1
substituting B=2
now the integral is [3+{1/(x+1)}+{2/(x-2)}]dx
=3x+ln(x+1)(x-2)^2+C

2006-10-05 11:04:08 · answer #3 · answered by raj 7 · 0 0

fedest.com, questions and answers